Would you be willing to pay more if AI robot waiters were introduced? The pivotal role of the need for uniqueness and perceived uniqueness - Ramadhan, Tri Sugiarti; Krisnanto, Aditya Budi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
Service robots have the potential to enhance customer experiences with their innovative technology, but many people still feel uncomfortable around them. While some customers are open to being served by robots, most still prefer interacting with humans.  This inconsistency highlights the need to explore why consumers choose robotic service restaurants over conventional ones.  This study aims to extend the existing literature by examining the need for uniqueness and perceived uniqueness as critical determinants of attitudes and willingness to pay more. To the best of the author's knowledge, there are few studies that explore these factors in the context of service robots, particularly in Indonesia. We surveyed 308 customers who dined at restaurants with robot waiters. Our analysis, using regression and Sobel, revealed that the need for uniqueness doesn't significantly affect how consumers feel about these restaurants or their willingness to pay more. However, perceived uniqueness positively affects both consumer attitudes and willingness to pay more, both directly and indirectly.  This means that while the need for uniqueness can motivate consumers to explore novel experiences like dining at a restaurant with robot waiters, restaurants must ensure that the overall experience meets or exceeds customer expectations to enhance positive attitudes and willingness to pay more.